Hubungan Antara Short Term Memory dengan Kemampuan Sintaksis pada Anak Prasekolah Usia 3-5 Tahun di TK IV dan KB IV Saraswati Denpasar - Widyantari, Ni Wayan Tika; Nugroho, Setyadi (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Short term memory is a memory that is responsible for holding and processing relevant information and at the same time, this will activate the repository language of lexical representations in long term memory. Syntax is an aspect of language that refers to grammatical rules, i.e., how words are combined into phrases and sentences correctly in grammar (White et al., 2017). Objectives: This study aims to determine the relationship between short term memory and the syntactic ability in preschool children aged 3-5 years at Kindergarten IV and Play Group IV Saraswati Denpasar. Methods: This research uses a quantitative method, an observational approach with a cross sectional study design. The population in this study were children 3-5 years old in Kindergarten IV and Play Group IV Saraswati Denpasar. The sampling technique used purposive sampling by taking 37 samples of children. Results: The results of the Spearman rank test show that short term memory ability and syntactic ability have a significance of 0.000 (ρ < 0.05) so that the alternative hypothesis (Ha) is accepted. The correlation test value (r) shows a figure of 0.938 and shows a positive correlation. Conclusion: There is a relationship between short term memory and the syntactic abilities of preschool children aged 3-5 years at Kindergarten IV and Play Group IV Saraswati Denpasar. Keywords: Short Term Memory, Syntax, Syntactic, Preschool Cognitive, Language